Przeciw formalizmowi. Teshigahary Hiroshiego dialog z tradycjami i współczesnością sztuk wizualnych w kinie - MAREK BOCHNIARZ; PRZEMYSŁAW SZTAFIEJ (Images)
Against formalism. Teshigahara Hiroshi’s dialogues with tradition and the present of visual cinematic art The authors examine Teshigahara Hiroshi’s little-known early documentary films Ikebana and Inochi, as well as his later historical films Rikyu and Go-hime. Their aim is to demonstrate how the director refers to the themes of art and the artist in the context of visual art and the work of his father, Teshigahara Sofo.